The enhancement of photosynthetic performance, water use efficiency and potato yield under elevated CO2 is cultivar dependent - Dahal, Keshav; Milne, Matthew A.; Gervais, Taylor (Frontiers in Plant Science, 2023)
As a fourth major food crop, potato could fulfill the nutritional demand of the growing population. Understanding how potato plants respond to predicted increase in atmospheric CO2 at the physiological, biochemical and molecular level is therefore important to improve potato productivity. Thus, the main objectives of the present study are to investigate the effects of elevated CO2 on the photosynthetic performance, water use efficiency and tuber yield of various commercial potato cultivars combined with biochemical and molecular analyses. We grew five potato cultivars (AC Novachip, Atlantic, Kennebec, Russet Burbank and Shepody) at either ambient CO2 (400 μmol CO2 mol−1) or elevated (750 μmol CO2 mol−1) CO2. Compared to ambient CO2-grown counterparts, elevated CO2-grown Russet Burbank and Shepody exhibited a significant increase in tuber yield of 107% and 49% respectively, whereas AC Novachip, Atlantic and Kennebec exhibited a 16%, 6% and 44% increment respectively. These differences in CO2-enhancement of tuber yield across the cultivars were mainly associated with the differences in CO2-stimulation of rates of photosynthesis. For instance, elevated CO2 significantly stimulated the rates of gross photosynthesis for AC Novachip (30%), Russet Burbank (41%) and Shepody (28%) but had minimal effects for Atlantic and Kennebec when measured at growth light. Elevated CO2 significantly increased the total tuber number for Atlantic (40%) and Shepody (83%) but had insignificant effects for other cultivars. Average tuber size increased for AC Novachip (16%), Kennebec (30%) and Russet Burbank (80%), but decreased for Atlantic (25%) and Shepody (19%) under elevated versus ambient CO2 conditions. Although elevated CO2 minimally decreased stomatal conductance (6-22%) and transpiration rates (2-36%), instantaneous water use efficiency increased by up to 79% in all cultivars suggesting that enhanced water use efficiency was mainly associated with increased photosynthesis at elevated CO2. The effects of elevated CO2 on electron transport rates, non-photochemical quenching, excitation pressure, and leaf chlorophyll and protein content varied across the cultivars. We did not observe any significant differences in plant growth and morphology in elevated versus ambient CO2-grown plants. Taken all together, we conclude that the CO2-stimulation of photosynthetic performance, water use efficiency and tuber yield of potatoes is cultivar dependent.